Growth and production of Katokkon (Capsicum chinense Jacq) chili plants in lowland applied with gibberellins and liquid organic fertilizer. Issue 1 (April 2020) - Kasim, N; Panggula, N D P; Haring, F; Ulfa, F; Dachlan, A; Widiayani, N; Yulsan, D
Abstract: This study aimed to determine the growth and production of katokkon chili plants ( Capsicum chinense Jacq.) in the application of gibberellins and liquid organic fertilizer. This research was conducted at the Experimental Farm of the Faculty of Agriculture, Universitas Hasanuddin, Makassar from May to October 2017. The research was conducted in the form of a two-factors factorial experiment. The first factor was gibberellins consisted of four levels namely 0 ppm, 25 ppm, 50 ppm and 75 ppm, and the second factor was liquid organic fertilizer consisted of three levels of 25 ml L −1, 50 ml L −1 and 75 ml L −1 with three replications. Results of the study show that application of gibberellins on the local chili plant of katokkon interacted with liquid organic fertilizer improved the vegetative growth of the plant. Gibberellin also significantly affected the production parameters of the local chili plant. The fruit weight per plant and per hectare decreased with the increased of gibberellin dosages. No significant effect of the use of liquid organic fertilizer found, however, the treatment of 75 ml L −1 showed better results in several research parameters.